Fatores associados ao Near Miss materno e neonatal em gestações gemelares - Lopes, Fernanda Nogueira Barbosa (2020)
Objective: To analyze the factors associated with maternal near miss (MNM) and neonatal near miss (NNM) in twin pregnancies. Methods: This is a cross-sectional study carried out on medical records of pregnant women with twins and their respective newborns, admitted for delivery at a public maternity reference in Fortaleza-Ceará, from January 2016 to December 2018.To identify MNM cases, the criteria proposed by the World Health Organization were used and to identify NNM cases, the following criteria were adopted: Apgar < 7 in the 5th minute, weight < 1,500 g, gestational age < 32 weeks, use mechanical ventilation or report of congenital malformation. The data were processed using SPSS version 23.0. Chi-square and Fisher's tests were used. Variables with p-value ≤ 0.20 were tested in multiple analysis using the Poisson regression model with robust variance. Variables with p-value < 0.05 in the multiple analysis were included in the final regression model. Results: In the population eligible for NNM analysis, there were 567 non-NNM twins and 130 considered NNM cases, totaling 697 studied twins, with an NNM rate of 171.9/1,000 live births. The following are associated with the NNM: primiparous PR 1.38 (1.03-1.85); > 3 previous pregnancies PR 1.93 (1.38-2.69); premature rupture of membranes RP 1.50 (1.70-2.12); intrauterine growth restriction PR 2.28 (1.53-3.33); premature labor PR 1.63 (1.13-2.35); resuscitation in the delivery room PR 1.80 (1.24-2.62) and transfusion of blood products PR 4.44 (3.14-6.28). For MNM, 390 women and their respective newborns were researched, of those, 6 women had MNM criteria and 384 without MNM criteria, the MNM ratio was 7.93/1,000 live births. Schooling <8 years (p = 0.016), heart disease (p = 0.007), monochorionic-monoamniotic pregnancies (p = 0.032), preeclampsia/eclampsia (p = 0.032), admission to the ICU are associated with MNM in twin pregnancies (p = <0.001), use of magnesium sulfate (p = <0.013), maternal blood transfusion (p = <0.001) and neonatal blood transfusion (p = <0.001). Conclusion: The factors associated with NNM were primiparous, > 3 previous pregnancies, premature rupture of membranes, restriction of intrauterine growth; premature labor, resuscitation in the delivery room and transfusion of blood products and MNM were education, heart disease, monochorionicmonoamniotic pregnancies, pre-eclampsia/eclampsia, ICU admission, use of magnesium sulfate, maternal and neonatal blood transfusion.